Cost-effectiveness analysis of adjuvant therapy with atezolizumab in Chinese patients with stage IB-IIIA resectable NSCLC after adjuvant chemotherapy - Chen, Ping; Yang, Qing; Li, Yinfeng; Jing, Xiaomei; Chen, Jing (Frontiers in Oncology, 2022)
Background: Atezolizumab was confirmed in the IMpower010 phase III study. The use of platinum-based chemotherapy in early-stage NSCLC can improve progression-free survival (PFS); however, the cost-effectiveness and potential economic impact of atezolizumab treatment in Chinese patients are unknown. Methods: Markov models were constructed based on follow-up data from the IMpower010 trial and assessed separately In the PD-L1 TC ≥ 1% stage II – IIIA group, all stage II – IIIA groups, and the intention-to-treat group (stage IB – IIIA), cost-effectiveness of adjuvant atezolizumab, Efficacy and safety data were obtained from the IMpower010 trial, and costs and utility values were derived from the literature and local surveys to estimate their incremental cost-effectiveness ratios (ICERs) compared with willingness-to-pay (WTP) thresholds in scenarios implementing patient assistance programs (PAP) or drug price negotiations. Univariate sensitivity analysis and probabilistic sensitivity analysis were performed to investigate the stability of the model results. Results: Compared with best supportive care, atezolizumab produced an additional 0.45 QALYs, 0.04 QALYs, and 0 QALYs in the PD-L1 TC ≥ 1% stage II – IIIA group, all stage II – IIIA groups, and the intention-to-treat group, and the ICERs were 108,825.37/QALY, 1,028,538.22/QALY, and 0/QALY, respectively. The ICERs all exceeded the WTP threshold of $27,354 per QALY (three times the per capita gross domestic product of China in 2022), and univariate sensitivity analysis showed that the price of atezolizumab played a crucial role in the model results. Probabilistic sensitivity analysis showed that the probability of cost-effectiveness of atezolizumab in the PD-L1 TC ≥ 1% stage II – IIIA group, all stage II – IIIA groups, and the intention-to-treat group (IB – IIIA) increased with increasing WTP threshold. Conclusion: From the perspective of China's health care system, in the PD-L1 TC ≥ 1% stage II – IIIA group, all stage II – IIIA groups, and the intention-to-treat group, the use of atezolizumab in the adjuvant treatment of patients with early-stage NSCLC after platinum-based chemotherapy is unlikely to be cost-effective. The implementation of PAP or price reduction negotiations for atezolizumab might be among the most effective measures to improve its cost-effectiveness.